Pengenaan Pajak Pada Transaksi Jual Beli Atas Tanah - Putu Ngurah Angga Darmawan; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Preferensi Hukum, 2025)
Income tax on sellers in land and building sale and purchase activities is regulated by government regulations. However, taxpayers' compliance in fulfilling their obligations may be affected by uncertainty in determining the value used for tax calculation. The main objective of this study is to establish a methodology for calculating the tax base in land sales and to examine the legal consequences for those who do not pay the tax that should be paid when transferring rights to land and or buildings. This research takes a normative legal approach. According to the research results, the taxpayer's actual or estimated value is used to determine the tax base. A comprehensive validation procedure is required to guarantee the correctness of the income tax levied. Fines, interest, or higher tax amounts may be imposed as administrative sanctions against parties who do not adequately fulfill their tax responsibilities. Audit of taxpayers' compliance in fulfilling tax payment obligations is required for the enforcement of such sanctions, taking into account both procedural and substantive aspects.